Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1002/dac.2345
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficiency comparison between distributed and co‐located MIMO systems

Abstract: SUMMARYEnergy efficiency (EE) is becoming more and more important in future wireless communications because of limited battery power in mobile terminals. In this paper, we compare EE of the distributed MIMO (D‐MIMO) and co‐located MIMO (C‐MIMO) in uplink systems. Taking into account both circuit and transmit power, we derive an analytical expression for EE of D‐MIMO and C‐MIMO systems in a composite Rayleigh‐lognormal channel. What is more, an optimization algorithm is proposed to get the optimal EE values whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…An energy-efficient link-adaptive transmission scheme for MIMO-OFDM systems has been proposed in [15] where the circuit power consumption is considered. The EE of the distributed MIMO (D-MIMO) and co-located MIMO (C-MIMO) in the uplink cellular systems have been compared in [16]. It has been demonstrated that D-MIMO systems are more energy-efficient than C-MIMO systems.…”
mentioning
confidence: 99%
“…An energy-efficient link-adaptive transmission scheme for MIMO-OFDM systems has been proposed in [15] where the circuit power consumption is considered. The EE of the distributed MIMO (D-MIMO) and co-located MIMO (C-MIMO) in the uplink cellular systems have been compared in [16]. It has been demonstrated that D-MIMO systems are more energy-efficient than C-MIMO systems.…”
mentioning
confidence: 99%
“…On the one hand, results show that our novel low-SE approximation is as accurate as the approximation of [2], but it has the advantage of a simplified formulation. On the other hand, our novel high-SE approximation is very tight with the actual EE-SE trade-off results in both the mid as well as high SE regimes, and is far more accurate than the approximation in [24]. This is due to the fact that the derivation of the approximations in [24] is based on lower and upper bounds instead of an exact formulation.…”
mentioning
confidence: 81%
“…On the other hand, our novel high-SE approximation is very tight with the actual EE-SE trade-off results in both the mid as well as high SE regimes, and is far more accurate than the approximation in [24]. This is due to the fact that the derivation of the approximations in [24] is based on lower and upper bounds instead of an exact formulation. As an application for our novel and accurate approximations, we study in Section V, both analytically and numerically, the effects of connecting additional RAUs to the user terminal (UT) on the system EE and how DMIMO compares with CMIMO in terms of EE, for both idealistic and realistic PCMs.…”
mentioning
confidence: 81%
See 2 more Smart Citations